Influence de la Consommation Alimentaire sur les Personnes Vivant Avec le VIH/Sida à l’Hôpital Militaire d’Abidjan (Côte d’Ivoire) Avant et Pendant la Prise des Antirétroviraux - Eba, Krou Philippe; Dje, Kouakou Martin; Kouassi, Kouadio Ignace; Amani, N’guessan Georges (European Scientific Journal, ESJ, 2019)
The success of HAART has increased the life expectancy of people living with HIV. In order to determine the influence of food consumption on PLWHIV / AIDS, a cohort study was conducted at the Abidjan Military Hospital (HMA) From January 2006 to December 2009, starchy foods, cereals and protein and mineral sources were mostly consumed by patients from different ethnic groups living with HIV before and during ARVs according to their dietary habits. Starchy foods such as plantain, cassava and yam were the most commonly consumed by the Akan ethnic group with respective rates of 88.1%, 83.8% and 79.9% before and 88.7%, 83.7% and 80.3% while taking ARVs. In contrast, sweet potato was the most consumed by non-Ivorians before and during ARVs. Food fortification has also been supplemented by cereals such as rice, maize and millet consumed mainly by the Mandé ethnic group during the taking of the said molecular combinations. In terms of protein sources and mineral salts, fish, meat and eggs were the most consumed by the Akan ethnic group while taking these ARVs. These foods rich in proteins, fats, carbohydrates, minerals and vitamins have been reinforced and healthy, varied and balanced consumption has been recommended to them in order to allow their body to better support the various side effects of these molecules and curbing opportunistic diseases. Taking antiretrovirals does not change the diet of people living with HIV / AIDS studied at the Abidjan Military Hospital. Le succès de la multithérapie antirétrovirale a augmenté l’espérance de vie des Personnes Vivant avec le VIH (PVVIH). En vue de déterminer l’influence de la consommation alimentaire sur les PVVIH/sida, une étude de cohorte a été menée à l’Hôpital Militaire d’Abidjan (HMA). De janvier 2006 à décembre 2009, des féculents, céréales, sources protéiques et sels minéraux ont été majoritairement consommés par des patients de différents groupes ethniques avant et pendant la prise des ARV selon leur habitude alimentaire. Les féculents: banane plantain, manioc et igname ont été les plus consommées par le groupe ethnique Akan avec des taux respectifs (88,1 ; 83,8 et 79,9 %) avant et (88,7 ; 83,7 et 80,3 %) pendant la prise des ARV. En revanche, la patate douce a été la plus consommée par les non ivoiriens avant et pendant la prise ARV. Par ailleurs, Le renforcement de l’alimentation a été aussi complété par les céréales telles que : riz, maïs et mil consommés majoritairement par le groupe ethnique Mandé. Au niveau des sources protéiques et sels minéraux : poisson, viande et œuf ont été les plus consommés par le groupe ethnique Akan. Ces aliments ont été renforcés et des consommations, saines, variés et équilibrés ont été conseillées à ceux-ci en vue de permettre à leur organisme de supporter au mieux les effets secondaires et freiner les maladies opportunistes. La prise des antirétroviraux ne changent pratiquement pas le régime alimentaire des PVVIH/sida étudié à l’HMA.